Connection of oral health related quality of life with caries in children with stunting: Descriptive study - Rafilia, Yuanne Nisrina; Sukmasari, Susi; Setiawan, Arlette Suzy; Indriyanti, Ratna (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: Stunting is one of the growth and development problems that causes a child's body to become shorter or very short in accordance with his/her age and exceeds the Standard Deviation (SD) set by the World Health Organization (WHO), namely < -2 SD. The condition of stunting also inhibits the development of the oral cavity which causes children suffering from stunting to be more susceptible to caries. Caries experienced by children will have a negative impact on a child's daily life and can affect the quality of his/her life. This research aimed to analyze the relationship between caries status of a child with stunting and his quality of life. Methods: The type of research used was a quantitative the descriptive research with correlational research method using correlational survey method with questionnaires conducted in Ciapus Village, Banjaran District, Bandung Regency. Samples were taken using purposive sampling technique with a sample size of 60 people. The time range used in this research was December 2023 – January 2024. The questionnaire used was The Early Childhood Oral Health Questionnaire. The Impact Scale (ECOHIS) was used to measure quality of life and the def-t index was used to measure the child's caries status. Results: The def-t index of stunted children in Ciapus Village was 6.46 which was considered as high in the category. Total percentage of ECOHIS questionnaire answers showed a value of 46.41% and was in the category of quite impactful. The results of the Spearman rank correlation calculation = 0.475, which meant that there was a fairly significant relationship. Conclusion: There is a weak relationship between oral health related quality of life and caries conditions in the oral cavity of stunted children, because poor quality of the child's oral cavity does not have a direct impact on the occurrence of caries.KEYWORDS: stunting, caries, children's quality of life, children's oral healthHubungan Oral Health Related Quality of Life dengan Karies pada Anak Stunting: studi deskriptif ABSTRAKPendahuluan: Stunting adalah salah satu permasalahan tumbuh kembang yang menyebabkan tubuh anak menjadi lebih pendek atau sangat pendek tidak sesuai dengan usia nya dan melewati Standar Deviasi (SD) yang ditetapkan World Health Organization (WHO) yaitu < -2 SD. Kondisi stunting juga menghambat perkembangan rongga mulut yang menyebabkan anak yang mengalami stunting lebih rentan terkena karies. Karies yang dialami oleh anak akan berdampak buruk terhadap kehidupan anak sehari-hari dan dapat mempengaruhi kualitas hidupnya. Penelitian ini bertujuan untuk menganalisis hubungan antara status karies anak stunting dengan kualitas hidupnya. Metode: Jenis penelitian yang digunakan yaitu penelitian deskriptif kuantitatif dengan metode penelitian korelasional menggunakan metode survei dengan kuesioner yang dilakukan di Desa Ciapus, Kecamatan Banjaran, Kabupaten Bandung. Sampel diambil dengan menggunakan teknik purposive sampling dengan jumlah sampel 60 orang. Rentang waktu yang digunakan dalam penelitian ini adalah bulan Desember 2023 – Januari 2024. Kuesioner The Early Childhood Oral Health. Impact Scale (ECOHIS) digunakan untuk mengukur kualitas hidup dan indeks def-t digunakan untuk mengukur status karies anak. Hasil: Indeks def-t dari anak stunting di Desa Ciapus adalah sebesar 6,46 yang termasuk kategori tinggi. Persentase total jawaban kuesioner ECOHIS menunjukkan nilai sebesar 46,41% dan termasuk kedalam kategori cukup berdampak. Hasil perhitungan korelasi rank spearman = 0,475 yang memiliki arti memiliki hubungan cukup signifikan. Simpulan: Terdapat hubungan yang lemah antara oral health related quality of life dengan kondisi karies pada rongga mulut anak stunting, karena kualitas rongga mulut anak yang buruk tidak memiliki dampak secara langsung terhadap terjadinya karies.KATA KUNCI: stunting, karies, kualitas hidup anak, kesehatan mulut anak